MARINE SEARCH AND RESCUE SYSTEM UTILIZING V-PASS-BASED PERSONAL LOCATION TRANSPONDER, AND SEARCH CONTROL METHOD THEREOF - LEE, Ju Hwan (2018)
The present invention relates to a marine search and rescue system utilizing a personal location transponder that is based on a fishing vessel port arrival and departure management system (V-PASS), the marine search and rescue system being characterized by sequentially comprising: a personal location transponder (PLT) (100) carried by a user on the sea; a fishing vessel port arrival and departure management system (V-PASS) (10), which is installed in a fishing vessel, and receives and transmits signals sent from the personal location transponder (100); a base station (3) including a transceiving antenna for receiving and relaying signals amplified and sent from the fishing vessel port arrival and departure management system (V-PASS) (10); and a distress information center (5) that transmits and receives signal information to and from the base station, wherein the signal sent from the personal location transponder is amplified in steps and provided to the distress information center (5) installed on land, thereby allowing an emergency rescue signal (SOS) sent by the user to be quickly confirmed and a rescue operation to be quickly executed. La présente invention concerne un système de recherche et de sauvetage maritime utilisant un transpondeur de localisation personnel qui est basé sur un système de gestion d'arrivée dans le port et de départ du port de navire de pêche (V-PASS), le système de recherche et de sauvetage maritime étant caractérisé en ce qu'il comprend séquentiellement : un transpondeur de localisation personnel (PLT) (100) porté par un utilisateur en mer ; un système de gestion d'arrivée dans le port et de départ du port de navire de pêche (V-PASS) (10), qui est installé dans un navire de pêche, et reçoit et transmet des signaux envoyés par le transpondeur de localisation personnel (100) ; une station de base (3) comprenant une antenne d'émission-réception pour recevoir et relayer des signaux amplifiés et envoyés depuis le système de gestion d'arrivée dans le port et de départ du port de navire de pêche (V-PASS) (10) ; et un centre d'informations de détresse (5) qui transmet et reçoit des informations de signal vers et depuis la station de base, le signal envoyé par le transpondeur de localisation personnel étant amplifié par étapes et fourni au centre d'informations de détresse (5) installé sur terre, ce qui permet de confirmer rapidement un signal de sauvetage d'urgence (SOS) envoyé par l'utilisateur et d'exécuter rapidement une opération de sauvetage. 본 발명은 어선 입출항관리시스템(V-PASS) 기반 개인휴대 위치발신장치를 활용한 해양수색구조 시스템에 관한 것으로, 해상에서 사용자가 휴대한 개인휴대 위치발신장치(Personal Location Transponder; "PLT")(100)와; 상기 개인휴대 위치발신장치(100)로부터 발신되는 신호를 제공받아 송신하는 어선에 설치된 어선 입출항관리시스템(V-PASS)(10)과; 상기 어선 입출항관리시스템(V-PASS)(10)으로부터 증폭되어 발신된 신호를 수신하여 중계하기 위한 송수신 안테나를 구비한 기지국(3); 및 상기 기지국으로부터 신호정보를 송수신하는 조난정보센터(5);를 순차적으로 구비하되, 상기 개인휴대 위치발신장치로부터 발신된 신호를 단계적으로 증폭하여 육상에 설치된 상기 조난정보센터(5)에 제공함으로써 사용자에 의해 발신되는 긴급구조신호(SOS)를 신속하게 확인하고 구조활동을 실행할 수 있도록 구성하는 것을 특징으로 한다.